Geomorphological observation in karst landforms in the mountains of Parnassos - Helikon - Giona (Greece) - ΠΑΠΑΔΟΠΟΥΛΟΥ ΒΡΥΝΙΩΤΗ, Κ.; ΜΠΕΛΛΟΣ, Θ. (Bulletin of the Geological Society of Greece, 2001)
Various karst landforms, on the surface or underground, of different ages and sizes were formed on the mountains of Parnassos, Helikon and Giona because of suitable lithological, tectonic and climate conditions. The landforms of Trummerkarren have big extension and they are connected by the microtectonic and the climate. Dolines exist on high elevations and their main direction is NW-SE. The number of poljes is smaller than the other landforms and they are a result of the geological, tectonic and geomorphological conditions on the three mountains. On the west side of mountain Giona were observed karst basins with directions NW-SE. the main of them were Taratsa, Gardenitsa,and Kampos. The geological base of them is limestone of zone of Parnassos with parts of flysch. On the basins exist karst peripheral levels which show the way which they were created (tectonic). After the comparison between poljes of Giona and poljes of Parnassos - Helikon the deduction is that all of them are polygenetic poljes with age of Mio-Pliocene which were created by calm tectonic conditions and hot and humid climate. The development of karst forms was determined by tectonic action. The landforms on the three mountains have direction of NW-SE and the type of that karst is called "Gerichtete karst". The bottom of all the poljes is level and it is consist of alluvial deposits. On the margins of the poljes exist unconnected talus. During the winter time flood appears at all the small drainage through ponors (lake polje).